Raw material optimization and stone tool engineering in the Early Stone Age of Olduvai Gorge (Tanzania). Issue 162 (8th January 2020) - Key, Alastair; Proffitt, Tomos; de la Torre, Ignacio
Abstract : For more than 1.8 million years hominins at Olduvai Gorge were faced with a choice: whether to use lavas, quartzite or chert to produce stone tools. All are available locally and all are suitable for stone tool production. Using controlled cutting tests and fracture mechanics theory we examine raw material selection decisions throughout Olduvai's Early Stone Age. We quantify the force, work and material deformation required by each stone type when cutting, before using these data to compare edge sharpness and durability. Significant differences are identified, confirming performance to depend on raw material choice. When combined with artefact data, we demonstrate that Early Stone Age hominins optimized raw material choices based on functional performance characteristics. Doing so flexibly: choosing raw materials dependent on their sharpness and durability, alongside a tool's loading potential and anticipated use-life. In this way, we demonstrate that early lithic artefacts at Olduvai Gorge were engineered to be functionally optimized cutting tools.